Control of radiation-conductive heat exchange at crystal growth from melt - Deshko, V.I.; Karvatskii, A.Ya.; Lenkin, A.V.; Lokhmanets, Yu.V. (Functional Materials, 2008)
The influence of radiation heat exchange in a crystal-melt system for different (from the point of view of optical properties) material classes and crystal growing methods (at constant crystal-melt system thickness and at a constant melt thickness) is considered. The general approach is based on using of modified numerical one-dimensional crystallization model at radiation-conductive heat exchange. The radiation heat transfer in a crystal-melt system provides conditions for faster front movement. In this case, most favorable conditions with large temperature gradients are created in systems with transparent crystal and opaque melt. At simultaneous crystal and melt "transparency" the temperature gradients in melt may decrease and cause stability loss of the directed crystallization. Розглядається вплив радіаційного теплообміну у системі кристал-розплав для різних з точки зору оптичних властивостей класів матеріалів і методів вирощування кристалів: при постійній товщині системи кристал-розплав і при постійній товщині розплаву. Загальний підхід оснований на використанні модифікованої чисельної одновимірної моделі кристалізації при радіаційно-кондуктивному теплообміні. Радіаційний теплоперенос у системі кристал-розплав забезпечує умови для швидшого переміщення фронту, при цьому найбільш сприятливі умови з великими градієнтами температури створюються у системах прозорий кристал - непрозорий розплав. При одночасній «прозорості» кристала і розплаву градієнти температури у розплаві можуть зменшуватися і приводити до втрати стабільності процесу направленої кристалізації. Рассматривается влияние радиационного теплообмена в системе кристалл-расплав для разных с точки зрения оптических свойств классов материалов и методов выращивания кристаллов: при постоянной толщине системы кристалл-расплав и при постоянной толщине расплава. Общий подход построен на использовании модифицированной численной одномерной модели кристаллизации при радиационно-кондуктивном теплообмене. Радиационный теплоперенос в системе кристалл-расплав обеспечивает условия для более быстрого перемещения фронта, при этом наиболее благоприятные условия с большими градиентами температуры создаются в системах прозрачный кристалл - непрозрачный расплав. При одновременной "прозрачности" кристалла и расплава градиенты температуры в расплаве могут уменьшаться и приводить к потере устойчивости направленной кристаллизации.